2017
DOI: 10.3390/en10101577
|View full text |Cite
|
Sign up to set email alerts
|

Battery State-Of-Charge Estimation Based on a Dual Unscented Kalman Filter and Fractional Variable-Order Model

Abstract: State-of-charge (SOC) estimation is essential for the safe and effective utilization of lithium-ion batteries. As the SOC cannot be directly measured by sensors, an accurate battery model and a corresponding estimation method is needed. Compared with electrochemical models, the equivalent circuit models are widely used due to their simplicity and feasibility. However, such integer order-based models are not sufficient to simulate the key behavior of the battery, and therefore, their accuracy is limited. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 46 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…Tian et al [96] used the UKF with a modified ECM to study the effects different temperatures and charge rates. Some variants of the UKF have also been reported [100][101][102][103][104][105][106][107]. In [100,102], an adaptive UKF (AUKF) adaptively adjusts the perturbation covariance of the state's value; the zero-state battery hysteresis model was selected to reduce the complexity [100].…”
Section: Reference Mae (%)mentioning
confidence: 99%
See 2 more Smart Citations
“…Tian et al [96] used the UKF with a modified ECM to study the effects different temperatures and charge rates. Some variants of the UKF have also been reported [100][101][102][103][104][105][106][107]. In [100,102], an adaptive UKF (AUKF) adaptively adjusts the perturbation covariance of the state's value; the zero-state battery hysteresis model was selected to reduce the complexity [100].…”
Section: Reference Mae (%)mentioning
confidence: 99%
“…The comparison showed that the AUKF has a better accuracy and convergence rate than the EKF, AEKF, and UKF. Cai et al [103] addressed the issue of the battery model accuracy. They proposed a fractional variable order model, which updates the value of the battery model adaptively.…”
Section: Reference Mae (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…The UKF was implemented in several studies for the SoC estimation of the batteries. As in References [5,6], an adaptive unscented Kalman filter (AUKF) is proposed for SoC estimation, which reduces the complexity by adaptively adjusting the covariance of state values and selecting a zero-state battery hysteresis model. However, from the implementation of the UKF algorithm, we can find that the position of the Sigma points directly affects the accuracy of the state estimation by the UKF algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In the traditional UKF algorithm [15][16][17][18][19], the covariance is a constant and cannot satisfy the real-time dynamic characteristics of the noise, which has a certain impact on the accuracy [20,21]. To eliminate this effect, the traditional UKF algorithm is improved by updating the covariance in real-time, which thus improves the accuracy of the UKF in this paper.…”
Section: Introductionmentioning
confidence: 99%